Utilization of Radio Frequency for Monitoring the Temperature of Hydroponic Plants Based on the Internet of Things - Dara Maulidia; Eva Darnila; RisaWandi (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
This research aims to develop a temperature monitoring system for hydroponic plants based on the Internet of Things (IoT), using the nRF24L01 radio frequency module. The system is designed to monitor the temperature of hydroponic plants, specifically spinach and chili, and to evaluate its range and efficiency compared to traditional methods such as GSM and Wi-Fi. With this technology, users can monitor and control the hydroponic environment in real-time through a smartphone, which can enhance the efficiency and effectiveness of plant cultivation. The research results indicate that the radio frequency module has a better data transmission range and higher reliability compared to traditional methods, making it an effective and practical solution for hydroponic monitoring. Additionally, this system provides significant benefits in improving plant growth and productivity by ensuring optimal environmental conditions. The use of IoT and radio frequency technology in this research demonstrates great potential for broader applications in agriculture, particularly in promoting more sustainable and efficient farming practices. These findings open up opportunities for further development in utilizing technology to support modern, connected, and smart agriculture.